2004
DOI: 10.1021/ol049928c
|View full text |Cite
|
Sign up to set email alerts
|

Dirhodium(II) Tetra(N-(dodecylbenzenesulfonyl)prolinate) Catalyzed Enantioselective Cyclopropenation of Alkynes

Abstract: Dirhodium tetrakis((S)-N-(dodecylbenzenesulfonyl)prolinate) (Rh(2)(S-DOSP)(4)) is an effective chiral catalyst for the enantioselective cyclopropenation of alkynes by methyl aryldiazoacetates. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 29 publications
0
54
0
1
Order By: Relevance
“…[7][8][9] Although high levels of enantioselectivity (up to 99 % ee) in cyclopropenations of terminal alkynes with aryldiazoacetates [7a] or arylvinyldiazoacetates [7b] under catalysis by [Rh 2 (S-dosp) 4 ] (4) have been reported by Davies and co-workers, the goal for the reaction with a-alkyl-a-diazoesters remains elusive because of the propensity to form a,b-unsaturated esters through a 1,2-hydride shift.…”
mentioning
confidence: 99%
“…[7][8][9] Although high levels of enantioselectivity (up to 99 % ee) in cyclopropenations of terminal alkynes with aryldiazoacetates [7a] or arylvinyldiazoacetates [7b] under catalysis by [Rh 2 (S-dosp) 4 ] (4) have been reported by Davies and co-workers, the goal for the reaction with a-alkyl-a-diazoesters remains elusive because of the propensity to form a,b-unsaturated esters through a 1,2-hydride shift.…”
mentioning
confidence: 99%
“…While complexes with α,α,α,α-and α,α,α,β-conformations, which have non-equivalent catalyst faces, are likely to induce low or no enantioinduction as their more accessible and kinetically active face is achiral. This previous proposal from Davies et al originates from their discovery of Rh2(S-DOSP)4 catalyst (Scheme 2) [36], which offered extraordinary enantioselectivity in a wide range of chemical transformations (up to 99% ee) [7,13,36,40,42,44,47,48,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This exceptional enantioselectivity of Rh2(S-DOSP)4 was proposed to originate from a favored α,β,α,β-arrangement of ligands adapted during catalysis.…”
Section: Ligand Blocking Groups Arrangementsmentioning
confidence: 99%
“…When the reaction was carried out at 40 °C, the desired product 3a could be obtained in 66% yield (entry 8). After screening BF 3 ·Et 2 O, it was found that acetone, CH 3 CN, DMF, and iodine did not give superior results in terms of either reactivity or stereoselectivity (entries [9][10][11][12].…”
Section: Paper Syn Openmentioning
confidence: 99%
“…8 Corey and co-workers also reported a significantly improved enantioselective cyclopropenation of ethyl diazoacetate with 1-alkynes using a new rhodium complex, Rh 2 (OAc)(DPTI) 3 , as a catalyst. 9 Although high levels of enantioselectivity (up to 99% ee) in cyclopropenations of terminal alkynes with aryldiazoacetates under catalysis by [Rh 2 (S-dosp) 4 ] have been reported by Davies and coworkers, 10 stereoselective syntheses of the corresponding cyclopropenylphosphonates using such a strategy remain scarce. 11 α-Diazophosphonates are phosphorus analogues of α-diazoacetates, and therefore could undergo a range of chemical transformations and the synthesis of varieties of functionalized phosphorous compounds.…”
mentioning
confidence: 99%